Implementation of nuchal translucency image‐scoring method during ongoing audit - Herman, A.; Dreazen, E.; Maymon, R.; Tovbin, Y.; Bukovsky, I.; Weinraub, Z. (Ultrasound in obstetrics & gynecology, 1999)
Objective The aim of this study was to evaluate the contribution of an ongoing audit, using the image‐scoring method, to the quality of nuchal translucency images and to set the basic standards required from the examiners. Design Evaluation of nuchal translucency images, before, during and after the implementation of an ongoing audit, without knowledge of the time period or the examiner. Subjects A total of 315 nuchal translucency scans were performed by three examiners. Methods Each of the retrospective, intermediate and prospective time periods included blind scoring of 105 images. The effect of the ongoing audit was examined by comparing the distribution of the quality groups and the mean final score between the time periods, for all cases and for each examiner separately. Improvement of the criteria was assessed by comparing the rate of scans meeting the demands between the time periods. Results The quality of the images improved significantly as the mean final score changed from 4.62 ± 0.21 to 6.19 ± 0.19 and to 6.91 ± 0.16 (p < 0.0001) and the rate of obtaining acceptable scans rose from 72% to 88% and to 92% (p < 0.001), respective to the three time periods. Whereas the three major criteria improved significantly before and after implementation of the audit (mid‐sagittal section from 48% to 94%, caliper placement from 60% to 75% and skin line from 19% to 77%), the minor criteria remained unchanged (image size 90%, amnion demonstration 25% and head position 77%). The average scores of two examiners, for whom improvement was more pronounced, were used to determine the basic standards required from examiners subjected to the audit as follows: unacceptable, none; intermediate, 5%; reasonable, 65%; excellent, 30%; with a mean final score of 7.25. Conclusions Implementation of an ongoing audit, using the image‐scoring method, proved to be an efficient method for surveillance and improving the quality of nuchal translucency images. We recommend centers or individuals practicing first‐trimester ultrasound screening to consider its routine utilization, in an unbiased and strict manner. Copyright © 1999 International Society of Ultrasound in Obstetrics and Gynecology